TPACK ICT oriented game-based long jump learning media - Kadek Jefry Dwi Sumarjono; Made Agus Wijaya; I Gede Suwiwa (Sriwijaya Journal of Sport, 2024)
This research aims to produce learning media in the form of video tutorials and videos of movement assignments on long jump material for class X SMA/SMK students. This development research uses the ADDIE development model design which consists of analysis, design, development, implementation, and evaluation. The population of the study consisted of 124 students. The sample for this research was 15 class X students at SMK Negeri 1 Singaraja, selected at random or random sampling. The research instrument uses a validity sheet for three validators, and an FCE / Formative Class Evaluation questionnaire for students. The data analysis technique uses quantitative-qualitative descriptive. The average score obtained from the evaluation results from content experts, design/media experts and PJOK practitioners was 95% and 96%, which means the category very good, and the implementation stage for individual and small group test students with an average of 3.00, which means category very good. Based on data analysis from research, the ICT TPACK game-based long jump learning media is suitable for use.